2016
DOI: 10.1161/circulationaha.115.019506
|View full text |Cite
|
Sign up to set email alerts
|

Report of the National Heart, Lung, and Blood Institute Working Group

Abstract: The National Heart, Lung, and Blood Institute convened a Working Group in January 2015 to explore issues related to an integrated data network for congenital heart disease (CHD) research. The overall goal was to develop a common vision for how the rapidly increasing volumes of data captured across numerous sources can be managed, integrated, and analyzed to improve care and outcomes. This report summarizes the current landscape of CHD data, data integration methodologies used across other fields, key considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 41 publications
0
5
1
Order By: Relevance
“…In the subgroup with available ancestry, whites undergoing CHS had higher survival than blacks, but their survival advantage also dissipated when compared to the race-matched general population. This finding contrasts with previous reports, although not directly comparable since these reports did not estimate SMR by race (41,53,54). This paradox does not seem to be due to differences in underlying conditions and may reflect better access to healthcare for blacks who underwent CHS in PCCC than those in the general population.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the subgroup with available ancestry, whites undergoing CHS had higher survival than blacks, but their survival advantage also dissipated when compared to the race-matched general population. This finding contrasts with previous reports, although not directly comparable since these reports did not estimate SMR by race (41,53,54). This paradox does not seem to be due to differences in underlying conditions and may reflect better access to healthcare for blacks who underwent CHS in PCCC than those in the general population.…”
Section: Discussioncontrasting
confidence: 99%
“…In the absence of longitudinal registries for CHD in the United States, assessment of long-term survival in this population remains incomplete. To fill this gap, the National Center on Birth Defects at the Centers for Disease Control and Prevention (CDC) outlined a public health research agenda for CHD that includes database linkage (40,41).…”
Section: Introductionmentioning
confidence: 99%
“…In pediatric cardiovascular disease, this has also been recognized as a priority, and The National Heart, Lung, and Blood Institute convened a working group in 2015 to develop a common vision for an integrated network for congenital heart disease research. The Working Group concluded that a comprehensive integration of data sources in the field may both improve clinical research efficiency and support novel analyses 13 .…”
Section: Commentmentioning
confidence: 99%
“…With the recent decline in federal research funding and the increase in costs and complexity of conducting multi-centre studies and clinical trials, investigators and research leaders have sought methods to improve efficiency. 1 One method has involved leveraging data from existing clinical registries. 16 Registries collect pre-specified clinical data for a variety of purposes, including outcomes tracking, national benchmarking, quality improvement, and public reporting, and are also used to facilitate research activities.…”
mentioning
confidence: 99%
“…The field of cardiology is well suited to take advantage of this methodology given the availability of multiple existing clinical registries and data-bases, standardised nomenclature and definitions, and a collaborative environment among centres. 1,3,8,9 Clinical registry data have been utilised to support prospective research in a few select studies in the field to date. 1012 However, little has been reported about experience with this method in pediatric cardiology.…”
mentioning
confidence: 99%